Evaluation of the Knowledge, Attitude and Perception of Healthcare Students on Antibiotics and Antibiotic Resistance: A Study in Central University, Ghana - Peace Doe; Cynthia Amaning Danquah; Kwasi Adomako Ohemeng; Gloria Awo Mashood; Jorindel Sepenoo; Kwame Ohene Buabeng; Michael Ofori (Journal of Tropical Pharmacy and Chemistry, 2023)
Students undergoing programmes in healthcare will play an important role in the management of antibiotic resistance which is still a global problem. Their knowledge and attitude should be adequately documented. This study is carried out to evaluate the knowledge, attitudes and perceptions of antibiotic use and antibiotic resistance among healthcare students in Central University, Ghana. In this study, 1027 students offering courses in pharmacy, nursing and physician assistantship participated in a survey to evaluate their knowledge, attitudes and perception on antibiotic use and antibiotic resistance. Data obtained was analyzed using STATA statistics DATA analysis software version 12.0. Descriptive statistics and chi-squared test was employed. Students displayed very good knowledge of antibiotic use and antibiotic resistance with students studying physician assistantship and nursing showing greater knowledge. The attitude of the respondents on the use of antibiotics was slightly above average. There was a significant difference (p = 0.029) between students’ programme of study and how they obtained their last course of antibiotics. Students displayed average knowledge on antibiotic use and antibiotic resistance but there is a need for more education to improve their perception and attitudes in order to contribute towards curbing the global problem of antibiotic resistance.